(untitled) (Malaysian Journal of Civil Engineering, 2020)
Ola-Olu intersection in Ilorin metropolis, Nigeria, is a 3-legged intersection in a typical urban centre of a developing economy. It is presently traffic warden controlled at morning peak period on weekdays and occasionally in the evening when there’s an event in a neighbouring public event centre that is expected to increase the traffic at the intersection. It is observed that the delay experienced at the intersection is quite high and traffic crashes at the intersection is a weekly occurrence. The study thereby aims at ameliorating the hazards by designing a fixed-time traffic signalization for the intersection. The objectives are to i. determine the geometric layout of the intersection ii. determine the traffic volume and vehicular turning movement pattern and iii. design and provide the signal timings at the T-intersection. Traffic volume survey and geometric layout survey were carried out at the intersection and analyzed to determine the optimum cycle length and signal setting using the Webster’s method. A 3-phase fixed time traffic signalization of 155 seconds cycle length was designed for an effective signal traffic control. The green time for phases 1, 2 and 3 are 102 seconds, 16 seconds and 22 seconds respectively. The implementation of the traffic signal will enhance both traffic flow and safety at the intersection.